Fabrication of micromold cavity for microreplication: A review - Ali, Mohammad Yeakub; Khan, Ahsan Ali; Mehfuz, R.; Aishah, S.; Hayati, N.; Hajar, N. (2008)
In this paper, various fabrication techniques for micromold cavity are reviewed and discussed. Silicon and lithography based fabrication were being used for years for the fabrication of micromold cavity. In the later stage direct fabrication techniques such as focused ion beam, micro electro discharge machining, laser micromachining, tool based micromilling, etc., become cost effective and popular. These micromold cavities were used for mass production of microcomponents. The fabrication processes, advantages and disadvantages of these processes are discussed in this paper. The processes are also compared for the ease of process selection for a particular fabrication.